2019
DOI: 10.1111/bpa.12780
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive low epidermal nerve fiber density in schwannomatosis patients provides a major parameter for diagnosis and differential diagnosis

Abstract: Schwannomatosis and neurofibromatosis type 2 (NF2) are two distinct neuro‐genetic tumor predisposition disorders, which, however, share some clinical and genetic features. While germline mutations in the NF2 gene are only found in NF2, a majority of schwannomatosis patients have germline mutations in the SMARCB1 or LZTR1 genes. The overlapping clinical phenotypes pose a serious challenge in differential diagnosis and in risk stratification of these two entities which is further complicated by frequent mosaicis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In our study, all schwannomatosis patients showed considerable reduction of the intraepidermal nerve fiber density, indicative of chronic small-fiber neuropathy as cause for the neuropathic pain experienced by schwannomatosis patients. Moreover, we found strong evidence that this reduction of intraepidermal nerve fiber density is pathognomonic for schwannomatosis in the spectrum of similar disorders especially in contrast to neurofibromatosis type 2 [13]. In analogy to other small-fiber entities [31,32], the combination of clinical pain pattern and the observed LEP abnormalities strongly suggests the presence of small-fiber neuropathy as an intrinsic disease feature of schwannomatosis.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In our study, all schwannomatosis patients showed considerable reduction of the intraepidermal nerve fiber density, indicative of chronic small-fiber neuropathy as cause for the neuropathic pain experienced by schwannomatosis patients. Moreover, we found strong evidence that this reduction of intraepidermal nerve fiber density is pathognomonic for schwannomatosis in the spectrum of similar disorders especially in contrast to neurofibromatosis type 2 [13]. In analogy to other small-fiber entities [31,32], the combination of clinical pain pattern and the observed LEP abnormalities strongly suggests the presence of small-fiber neuropathy as an intrinsic disease feature of schwannomatosis.…”
Section: Discussionsupporting
confidence: 54%
“…Regarding LEP amplitudes, no differences were detected in the patient group compared to matched controls (N2: exhibited a significant reduction of intraepidermal nerve fiber density (1.85 ± 0.92/mm) in comparison to age-adjusted reference-values (1.7-5.7/mm) [12] with a mean deviation from the age-dependent reference value of 1.84 ± 1.24/mm (Figure 4). Please note that the skin biopsy results presented here are a subset of data published in 2020 [13]. Interestingly, the observed reduction in intraepidermal nerve fiber density (IENFD) was neither associated with lesion burden as assessed by MR neurography (MRN), nor did it show any significant correlation with laser-evoked potentials (LEP) parameters.…”
Section: Laser Evoked Potentialsmentioning
confidence: 73%
See 1 more Smart Citation
“…Farschtschi et al [24] measured the intraepidermal nerve ber density (IEND) of skin biopsies and found that the IEND of patients with schwannomatosis (97%) was signi cantly lower than the standard reference, while fewer than half (44%) of NF2 patients had such low IEND. (6) Louvrier et al [25] suggested that the key to differential diagnosis between NF2 and schwannomatosis is the use of an ampli cation-based method to sequence tumor suppressor genes in NF2: SMARCB1, LZTR1, SWI/SNF-related matrix-associated actindependent regulator of chromatin subfamily E member 1 (SMARCE1) and suppressor of fused homolog (SUFU).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…To assess intraepidermal nerve fiber densities (IENFD), skin punch biopsies were performed in four patients, using a standardized procedure [20,21]. Eight mm punch biopsies were taken 10 cm above the lateral malleolus of the right foot.…”
Section: Skin Biopsiesmentioning
confidence: 99%